Application of a developmental assessment tool by social workers practicing foster care in the Far East Rand, Ekurhuleni. - Khoza, Sibongile (My University, 2011)
The South African welfare system has evolved over time from a residual approach influenced by apartheid to a developmental approach reflecting the objectives of a democratic and a developmental state. The research study aimed to gain an understanding of assessment as one of social work intervention by investigating the experiences of social workers providing foster care services using the developmental assessment tool. Some of the objectives of the study were to explore social workers’ views about the factors contributing to the tool not being used and to identify the challenges that social workers face in using the tool. This qualitative study used phenomenology as a research design. Ten individual semi-unstructured interviews were conducted using an interview schedule. Themes were used to classify and analyze data. The findings indicated that there were benefits in using the developmental assessment tool. It was also found that some respondents were not using the assessment tool regularly and the factors inhibiting the use of the developmental assessment tool were identified. Lastly, the participants’ perceptions of the assessment tool were shared with the researcher and possible amendments to the developmental assessment framework were identified by them. Some of the conclusions that were drawn out of the research study are the following: There is evidence that using the developmental assessment tool may have had a beneficial influence on the provision of services using a developmental approach to social welfare, thus contributing towards social development. There is a need to synchronize services at the macro and micro levels that will create an enabling environment for providing assessment services where the professional roles are undertaken effectively and the services are provided within the parameters of a developmental social welfare system.